Case report: Imaging features of aorta-right atrial tunnel in a dog using two-dimensional echocardiography and computed tomography - Kim, Geunha; Ji, Yewon; Jeong, Ho-Gyun; Lee, Taekwon; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2023)
A 7-year-old castrated male Pomeranian dog weighing 5 kg presented with a right-sided continuous murmur without any clinical signs. Thoracic radiographs indicated cardiomegaly and right atrial (RA) bulging. Echocardiography revealed a tunnel originating from the right coronary sinus of Valsalva and terminating in the RA. Contrast echocardiography revealed pulmonary arteriovenous anastomoses. Computed tomography (CT) demonstrated a tortuous shunting vessel that originated from the aorta extending in a ventral direction, ran along the right ventricular wall, and was inserted into the RA. Based on these diagnostic findings, the dog was diagnosed with the aorta-RA tunnel. At the 1-year follow-up visit without treatment, the dog showed no significant change except for mild left ventricular volume overload and mildly decreased contractility. To the best of our knowledge, this is the first case report of an aorta-RA tunnel that has been described in detail using echocardiography and CT in a dog. In conclusion, the aorta-RA tunnel should be included in the clinical differential diagnoses if a right-sided continuous murmur is heard or shunt flow originating from the aortic root is identified.